2014
DOI: 10.5489/cuaj.1890
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative parameters to predict incidental (T1a and T1b) prostate cancer

Abstract: Cite as: Can Urol Assoc J 2014;8(11-12):e815-20. http://dx.doi.org/10.5489/cuaj.1890 Published online November 24, 2014. AbstractIntroduction: Prostate cancer has been found incidentally in transurethral resection of the prostate (TURP) specimens without prior diagnosis in 5% to 13% of the patients. We evaluated whether incidental prostate cancer (stages T1a and T1b) could be predicted preoperatively. Methods: TURP was performed in 307 patients between 2006 and 2011. Patient age, prostate-specific antigen (PSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
3
20
1
2
Order By: Relevance
“…In literature, incidental prostate cancer (iPCa) rates vary depending on preoperative factors, such as patient age, preoperative prostate-specific antigen (PSA), prostate volume, and preoperative biopsy performance [8][9][10][11][12]. Recently, we additionally supported the idea that the surgical procedure itself has an influence on iPCa detection, as we demonstrated that HoLEP provides a superior iPCa detection rate compared to bipolar transurethral resection of the prostate (TURP) in a matched pair analysis [8].…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…In literature, incidental prostate cancer (iPCa) rates vary depending on preoperative factors, such as patient age, preoperative prostate-specific antigen (PSA), prostate volume, and preoperative biopsy performance [8][9][10][11][12]. Recently, we additionally supported the idea that the surgical procedure itself has an influence on iPCa detection, as we demonstrated that HoLEP provides a superior iPCa detection rate compared to bipolar transurethral resection of the prostate (TURP) in a matched pair analysis [8].…”
Section: Introductionmentioning
confidence: 60%
“…The quality of our matching was verified by almost identical preoperative baseline patient characteristics regarding age, preoperative PSA, preoperative prostate volume, PSA density, and preoperative biopsy rates. This is particularly critical as those parameters have been shown to be predictive for iPCa after desobstruction [8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, prostate cancer has been identified in TURP specimens without prior diagnosis in 5 to 13% of patients [6]. A recent study by Sakamoto et al found incidental prostate cancer in 10% of patients who underwent TURP, with 4% of the total cohort having stage T1b and/or Gleason ≥7 [6].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Sakamoto et al found incidental prostate cancer in 10% of patients who underwent TURP, with 4% of the total cohort having stage T1b and/or Gleason ≥7 [6]. In a larger cohort studied by Otto et al, 11/771 patients had incidental prostate cancer, 10 of whom had Gleason grade 3+3 disease and only one with Gleason grade 3+4 disease.…”
Section: Discussionmentioning
confidence: 99%